2022
DOI: 10.3390/ijms23105418
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Dynamics in Cocaine’s Neurotoxicity

Abstract: The dynamic balance of mitochondrial fission and fusion maintains mitochondrial homeostasis and optimal function. It is indispensable for cells such as neurons, which rely on the finely tuned mitochondria to carry out their normal physiological activities. The potent psychostimulant cocaine impairs mitochondria as one way it exerts its neurotoxicity, wherein the disturbances in mitochondrial dynamics have been suggested to play an essential role. In this review, we summarize the neurotoxicity of cocaine and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 176 publications
(213 reference statements)
4
10
0
Order By: Relevance
“…Thus, analysis of the brain of cocaine‐intoxicated male and female mice revealed the presence of sex‐independent changes in proteins that are crucial for maintenance of mitochondrial homeostasis. These data are consistent with the presence of cocaine‐induced mitochondrial alterations under our experimental conditions and are in full agreement with what was previously published by other independent groups (Funakoshi et al., 2019; Thangaraj et al., 2020; Thornton et al., 2021; Wen et al., 2022).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, analysis of the brain of cocaine‐intoxicated male and female mice revealed the presence of sex‐independent changes in proteins that are crucial for maintenance of mitochondrial homeostasis. These data are consistent with the presence of cocaine‐induced mitochondrial alterations under our experimental conditions and are in full agreement with what was previously published by other independent groups (Funakoshi et al., 2019; Thangaraj et al., 2020; Thornton et al., 2021; Wen et al., 2022).…”
Section: Resultssupporting
confidence: 94%
“…This hypothesis assumes compromised mitochondrial homeostasis after repetitive cocaine exposure, a cocaine-induced effect that was previously shown by several research groups (Funakoshi et al, 2019;Thangaraj et al, 2020;Wen et al, 2022;reviewed in Thornton et al, 2021), and found in the in vitro (Figure 5) and in vivo (Figure 4) experiments described here. In particular, mitochondria hyperpolarisation in cocaine-treated cells (Figure 5d) indicated an accumulation of H + protons in the IMS, suggesting a downstream block of oxidative phosphorylation (as previously reported; Cunha-Oliveira et al, 2013a, 2013bYuan & Acosta, 2000) at the level of the ETC Complex V, where, under physiological conditions, the H + gradient is dissipated to generate ATP.…”
Section:  Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the relationship between altered CCF in OFC and the duration of cocaine abuse suggests that this alteration may follow local neurotoxic or neuroplastic effects 49 . This observation is consistent with evidence from animal studies that shows that repeated exposure to cocaine can induce long‐lasting changes in brain morphology, including inhibition of neurite extension, reduction in endoplasmatic reticulum dilation, abnormal lysosomal proteolysis and altered neuronal mitochondrial dynamics 50 . Notably, these cocaine‐dependent cellular and molecular adaptations have been associated with changes in the dynamics of gene expression mediated by epigenetic changes, including DNA methylation, histone modifications and microRNAs 51 .…”
Section: Discussionsupporting
confidence: 80%
“…49 This observation is consistent with evidence from animal studies that shows that repeated exposure to cocaine can induce long-lasting changes in brain morphology, including inhibition of neurite extension, reduction in endoplasmatic reticulum dilation, abnormal lysosomal proteolysis and altered neuronal mitochondrial dynamics. 50 Notably, these cocainedependent cellular and molecular adaptations have been associated…”
Section: Correlations With Cocaine Use Characteristics Impulsivity Sc...mentioning
confidence: 99%